Analisis Strategi Komunikasi Pemasaran pada Unit Komersialisasi Non-Transportasi (KNA) PT. Kereta Api Indonesia (Persero) Daerah Operasi 7 Madiun - Septiarini, Silvi; Priyanto, Priyanto; Wardani, Galuh Kusuma (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2024)
PT Kereta Api Indonesia (Persero) holds significant land assets and offers various service products in strategic locations. However, the Non-Transport Commercialization Unit (KNA) remains relatively underrecognized. To enhance its visibility and revenue, the KNA Unit needs to increase its engagement with potential partners and more effectively promote its services. This research aims to analyze the marketing communication strategies employed by the KNA Unit in Operational Area 7 Madiun. Utilizing a descriptive qualitative approach and insights from three field experts, the study identifies nine key elements in the KNA's marketing communication strategy: advertising, online communication and social media, mobile communication, direct marketing, events and experiences, word of mouth, publicity and public relations, personal selling, and packaging. The findings indicate that the KNA Unit currently utilizes six of these nine elements. While these methods are effective, there is still potential for further improvement. Optimizing these strategies could significantly enhance engagement, increase visibility, and boost overall revenue. This research provides valuable insights for refining marketing approaches to achieve better outreach and commercial success.